Analisis Produksi Ozon dalam Reaktor Dielectric Barrier Discharge Plasma (DBDP): Pengaruh Impedansi Elektroda Spiral - Restiwijaya, Maryam; Nur, Muhammad; Winarni, Tri A (BERKALA FISIKA, 2014)
Analysis of spiral-cylinder DBDP reactor on atmospheric pressure was done to explain spiral electrode impedance influence on ozone production. Variation of coil number (N): 10, 20, 30, 40, and 50 coil spiral applied to the spiral electrodes. Spiral electrode made of a copper wire with 0.4 mm in diameter and the inner and outer coils of each was 20 mm and 20.4 mm. Pyrex Tubing in diameter 3 cm and a thickness of 1 mm serves as a dielectric barrier cover spiral electrode. Cylindrical electrodes made from a copper plate with a length of 13.70 cm and thickness of 0.47 mm. a High voltage of AC has been used with a voltage up to 10 kV with frequency of 16 kHz. Free air supplied into the reactor with air flow rate of 6 L/minute. The results showed that at a constant N, ozone concentration decreased with the increasing value of the impedance (Z). Reactor DBDP most effective in terms of electricity consumption is on the DL = 20 mm, DK = 0.4 mm, and the number of coil N = 10 coils of wire with a power that is as high as 177.60 Watt andÂ Z=3,60x105â„¦. Keywords : Number of coil, Spiral-cylinder electrodes, Ozone concentrations